Proton-mediated photoprotection mechanism in photosystem II - Sugo, Yu; Ishikita, Hiroshi (Frontiers in Plant Science, 2022)
Photo-induced charge separation, which is terminated by electron transfer from the primary quinone QA to the secondary quinone QB, provides the driving force for O2 evolution in photosystem II (PSII). However, the backward charge recombination using the same electron-transfer pathway leads to the triplet chlorophyll formation, generating harmful singlet-oxygen species. Here, we investigated the molecular mechanism of proton-mediated QA⋅– stabilization. Quantum mechanical/molecular mechanical (QM/MM) calculations show that in response to the loss of the bicarbonate ligand, a low-barrier H-bond forms between D2-His214 and QA⋅–. The migration of the proton from D2-His214 toward QA⋅– stabilizes QA⋅–. The release of the bicarbonate ligand from the binding Fe2+ site is an energetically uphill process, whereas the bidentate-to-monodentate reorientation is almost isoenergetic. These suggest that the bicarbonate protonation and decomposition may be a basis of the mechanism of photoprotection via QA⋅–/QAH⋅ stabilization, increasing the QA redox potential and activating a charge-recombination pathway that does not generate the harmful singlet oxygen.